Local gravity measurement by using the minimized period of rod pendulums - Sithipong, Saichon; Koontragool, Bacha (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2024)
In this paper, the results of determination of the local gravity by using the minimized period rod pendulums as the gravimeter have been presented. The studying used five rod pendulums of different lengths and test at a location that has the latitude of 18°39’43’’ N and elevation of 300 meters above MSL. Results from this study indicated that, by 12 trials of timing of 100 oscillation cycles of the rod pendulums with the initial angular amplitude less than 2°, the experimental local gravity obtained from the minimized period rod pendulum was 9.800 ± 0.008 m/s2. Compared with the calculated local gravity, 9.7847 m/s2, the error was 0.2 %, approximately.